Lipo-Polysaccharide Induces Bacterial Autophagy in Cancer Cells As an Anticancer Therapy - O. Hadi, Abas; Ozkan, Ozcan; Mazeel Abed, Saif; Kadhim Hussein, Karrar; Mohammed Gaila, Karrar (Journal of Neonatal Surgery, 2025)
Lipo-polysaccharides (LPS) derived from Escherichia coli (ATCC 8739) have emerged as promising anticancer agents due to their ability to induce bacterial autophagy in cancer cells. This study explores the effects of LPS on breast cancer cell lines, specifically MCF-7 and MDA-MB-231. Our investigation reveals that LPS treatment results in significant up-regulation of genes associated with the Toll-like receptor (TLR) stimulation pathway and autophagy-related processes. This up-regulation suggests that LPS not only enhances immune responses but may also work synergistically with conventional chemotherapy, potentially improving treatment outcomes for breast cancer patients. The mechanism by which LPS induces autophagy involves activation of immune signaling pathways, which could lead to increased apoptosis in cancer cells. Furthermore, our results indicate that LPS treatment significantly decreases cell viability in both MCF-7 and MDA-MB-231 cell lines, supporting its role in promoting cell death. These findings highlight the potential of LPS as a novel therapeutic agent in translational oncology research, providing a basis for further studies aimed at integrating LPS into existing breast cancer treatment protocols. Overall, LPS presents a compelling avenue for enhancing the efficacy of current cancer therapies and warrants further investigation in clinical settings .